Fan Culture and Female Spectatorship in the British Silent Cinema - Stead, Lisa (2006)
This study of female fan audiences across the period 1918 to 1928 seeks to engage and readdress conceptions of spectatorship and consumption in silent cinema specific to the British female experience. In focusing upon the film fan magazineÃÂÃÂ¢ÃÂÃÂÃÂÃÂs ability to offer a platform for the voice of female fans, I explore how fan discourses relate to the struggle between dominant representation and self-representation in the cultural construction of modern British femininity and female spectatorship, progressing towards a exploration of womenÃÂÃÂ¢ÃÂÃÂÃÂÃÂs interaction with female star images as fundamentally entwined with notions of ÃÂÃÂ¢ÃÂÃÂÃÂÃÂnew womanÃÂÃÂ¢ÃÂÃÂÃÂÃÂ and female consumption.